The role of EGCG in breast cancer prevention and therapy - Adriana Cruz Afonso Romano (2020)
Background: Breast cancer is the most frequent cancer in women. Green tea has been studied for breast cancer chemopreventive and possibly chemotherapeutic effects due to its high content in polyphenolic compounds, including epigallocatechin-3-gallate (EGCG). Method: This review is based on a literature research that included papers registered on the Medline(c) database. The research was conducted through PubMed, with the application of the following query: "EGCG"AND "breast cancer". The result was a total of 88 articles in which this review stands on. Results: In vitro, EGCG shows antioxidant or pro-oxidant properties depending on the concentration and exposure time. EGCG blocks cell cycle progression and modulates signaling pathways that affects cell proliferation and differentiation. EGCG also induces apoptosis, negatively modulates different steps involved in metastasis and targets angiogenesis by inhibiting VEGF transcription. In vivo, investigations have shown that oral administration of EGCG results in reduction of tumor growth and in antimetastatic and antiangiogenic effects in animal xenograft and allograft models. Discussion: Much remains unknown about the molecular mechanisms involved in the protective effects of EGCG on mammary carcinogenesis. In addition, more studies are necessary to determine the potential toxicity of EGCG at higher doses and to elucidate its interactions with other drugs. Conclusion: A protective effect of EGCG has been shown in different experimental models and under different experimental conditions, suggesting clinical implications of EGCG for breast cancer prevention and therapy. The data presented in this review support the importance of further investigations.